Relationship of breast volume, obesity and central obesity with different prognostic factors of breast cancer - Daniel María Lubián López (Nature Portfolio, 2021)
Abstract The objective of this study was to investigate whether the BC tumor biology in women with larger breast volume, in obese women and especially in women with central adiposity at the moment of diagnosis of BC is more aggressive than in those women without these characteristics. 347 pre- and postmenopausal women with a recent diagnosis of BC were analyzed. In all patients, anthropometric measurements at the time of diagnosis was collected. In 103 of them, the breast volume was measured by the Archimedes method. The Breast volume, BMI, WHR and the menopausal status were related to different well-known pathological prognostic factors for BC. At the time of diagnosis, 35.4% were obese (BMI > 30 kg/m2), 60.2% had a WHR ≥ 0.85, 68.8% were postmenopausal and 44.7% had a breast volume considered "large" (> 600 cc). Between patients with a large breast volume, only a higher prevalence of ER (+) tumors was found (95.3% vs. 77.2%; p = 0.04) compared to those with small breast volumes. The obese BC patients showed significantly higher rates of large tumors (45.5% vs. 40.6%; p = 0.04), axillary invasion (53.6% vs. 38.8%; p = 0.04), undifferentiated tumors (38.2% vs. 23.2%) and unfavorable NPI (p = 0.04) than non-obese women. Those with WHR ≥ 0.85 presented higher postsurgical tumor stages (61.7% vs. 57.8%; p = 0.03), higher axillary invasion (39.9% vs. 36.0%; p = 0.004), more undifferentiated tumors (30.0% vs. 22.3%; p = 0.009), higher lymphovascular infiltration (6.5% vs. 1.6%; p = 0.02), and a higher NPI (3.6 ± 1.8 vs. 3.2 ± 1.8; p = 0.04). No statistically significant differences were found according to menopausal status. We conclude that obesity, but especially central obesity can be associated with a more aggressive tumour phenotype. No relation between breast volume and tumoral prognostic factors was found, except for a higher proportion of ER (+) tumor in women with higher breast volume.